INFLUENCE OF SOME FACTORS ON ADHESION STRENGTH IN THE FORMATION OF WATER-BASED FINISHES ON BEECH PLYWOOD - Angelski, Dimitar; Atanasova, Krasimira (Innovation in Woodworking Industry and Engineering design, 2021)
Adhesion strength is an indicator of the coating’s detachment resistance from the base. The magnitude of the adhesion strength depends on the nature of the lacquer system, the type and state of the substrate, and the film formation conditions. In this study, a water-based varnish system was applied to beech plywood. The influence of а sandpaper grit size used and the time between а sanding and coating processes has been determined.